A Comparative Study on Learning styles and Strategies of High and Low Preforming Students on Mathematics - Ghimire, Ram Chandra (Interdisciplinary Research in Education, 2023)
The students in a class are diverged from many perspectives, among such perspectives their learning styles and strategies is one of the major. Basically, we as a teacher rather used to notice the learning styles and strategies of our students, we just motivated to categorize our students as high performer or low performer. In this context, this is a case study research on the topic 'A comparative study on learning styles and strategies of high and low performing students on mathematics' with the objectives to compare the learning strategies used by high and low performing students in mathematics. For which, four (two from each categories) students were selected purposively on the basis of their performance in mathematics as the key research participants from a higher secondary level. The identification of their learning strategies are based on four subheadings as readiness for learning, pre-knowledge of the content, process for learning and solving a problem. With the prolong engagement with participants, the study concluded with the various differences as well as similarities in each category and on the basis of such differences and similarities, the study further emphasized to be aware about their learning styles and strategies is more beneficial to create the meaningful teaching learning environment in the classroom.